2006
DOI: 10.1021/es052059h
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Mediated Oxidation of Antimony(III) by Oxygen and Hydrogen Peroxide Compared to Arsenic(III) Oxidation

Abstract: Antimony is used in large quantities in a variety of products, though it has been declared as a pollutant of priority interest by the Environmental Protection Agency of the United States (USEPA). Oxidation processes critically affect the mobility of antimony in the environment since Sb(V) has a greater solubility than Sb(lll). In this study, the cooxidation reactions of Sb(lIl) with Fe(ll) and both O2 and H2O2 were investigated and compared to those of As(III). With increasing pH, the oxidation rate coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 39 publications
5
49
0
Order By: Relevance
“…In contrast, H 2 O 2 -linked oxidation is much faster, with a half-life of 118 days for 1 M H 2 O 2 held at pH 8.0 (99,100). Several other oxidants also have the potential to oxidize Sb(III) to Sb(V), including natural and synthetic Fe and Mn oxyhydroxides (101,102), humic acids (103), and iodate (104). In addition, the oxidizing capacities of Fe and Mn oxyhydroxides can transform As species (105,106), and the amorphous Fe and Mn oxyhydroxides present in natural water and sediment also play a detoxifying role by adsorbing and oxidizing Sb(III).…”
Section: Microbial Antimony Cyclementioning
confidence: 99%
“…In contrast, H 2 O 2 -linked oxidation is much faster, with a half-life of 118 days for 1 M H 2 O 2 held at pH 8.0 (99,100). Several other oxidants also have the potential to oxidize Sb(III) to Sb(V), including natural and synthetic Fe and Mn oxyhydroxides (101,102), humic acids (103), and iodate (104). In addition, the oxidizing capacities of Fe and Mn oxyhydroxides can transform As species (105,106), and the amorphous Fe and Mn oxyhydroxides present in natural water and sediment also play a detoxifying role by adsorbing and oxidizing Sb(III).…”
Section: Microbial Antimony Cyclementioning
confidence: 99%
“…Abiotic oxidation of Sb III by different natural oxidants has been studied: synthetic and natural Fe and Mn oxyhydroxides, [90,91] hydrogen peroxide [70,[92][93][94] and iodate. [95] Oxidation of Sb III with hydrogen peroxide and iodate is pHdependent: no oxidation is observed below pH 9 because formation of Sb(OH) -4 is needed for oxidation to occur.…”
Section: Presence Of Thermodynamically Unstable Speciesmentioning
confidence: 99%
“…Since antimony is initially introduced into the environment as stibnite (Sb 2 S 3 ), oxidation of Sb (III) to Sb (V) plays a critical role in understanding the mobility and fate of Sb in the water system. Several potential oxidants have been indicated in publications that might facilitate the oxidation of Sb (III) yet no quantitative data has been observed (Belzile et al 2001;Filella et al 2007;Leuz 2006;Leuz et al 2006;Leuz and Johnson 2005;Quentel Leuz and Johnson (2005) found that O 2 as the sole oxidant of Sb(III) appeared to be extremely slow in homogenous aqueous solutions under environmental conditions. No significant oxidation of Sb (III) with O 2 was observed within 200 days at pH range of 3.6-9.8, which covers the full pH range of our studies.…”
Section: Distribution Of Total Antimonymentioning
confidence: 99%
“…A hypothetical reaction model dominated by Fenton reaction was first proposed by Leupin and Hug (2005) in the iron-mediated oxidation and removal of arsenic in the groundwater. Leuz et al (2006) According to the compositional analysis of Xikuangshan stibnite ores, the ores generally contained an iron-mineral (mainly pyrite with trace amount of pyrrhotite and sphalerite) composition of 3.2% compared to antimony abundance of 2.43% (Table 3; Fan et al 2004). The pyrite might have been washed down together with the stibnite and gone through the following oxidation reactions with antimony.…”
Section: Distribution Of Total Antimonymentioning
confidence: 99%